The nature of work of street-based prostitutes in Iloilo City. - Lauron, Syvel S.
Prostitutes are frequent victims of violent crimes such as abuses, assaults, rape or even death threats as well as they are prone to health related diseases. Reports of violence are particularly compelling when one recognizes that a substantial proportion of prostitutes begin working while still minors. The issue of AIDS has added urgency to efforts to understand prostitutes and their clients. Concern over prostitution has led to the formation of local organizations and task forces designed specifically to address the issue in many communities. The study was undertaken to know the nature of work of street-based female prostitutes in Iloilo City. It generally aims to describe the nature of work of the street-based prostitutes in Iloilo City by (1) knowing the profile of street-based prostitutes in Iloilo City; (2) knowing the manner by which street-based prostitutes solicit their customers; (3) describing the services offered by the street-based prostitutes to their customers and manner by which they are paid for these services; (4) knowing how street-based prostitutes in Iloilo City protect themselves against work related diseases and hazards. The researcher used snowball samp0ling in choosing the respondents. The data was gathered using interview schedule and analyzed using simple frequency counts and percentages. For this study, thirty-one street-based prostitutes with ages ranging from thirteen years old to fifty two years old. The study reveals that most of the respondents started in their early teenage years. Most of them are in the early twenties and late twenties. However, many of them reach high school and few finished college. It further shows that majority of the respondents solicit customers with the help of the pimp. Respondents offer sexual intercourse, oral sex, and massage to their customer. At the same time they are paid according to the kind of sexual services that they offer to their customer. In addition, the place where they look for customers, age and physical appearance contribute to their net income. Furthermore, prostitutes regularly visit health facilities such as that of Process Foundation, health centers, and private hospital clinics to undergo their regular pap-smearing check-up. They also encourage their customers to use condom during their sexual activities. Moreover, to avoid being caught by the policemen, they undergo pap-smearing and bring with them their smearing card results. Those without smearing cards, solicit customers insides videoke bars along the street. As for recommendations, the researcher suggests the increase the number of sample size to assure the reliability and validity of the study. Other research questions have to be pursued further such as; (1) why did they choose to become prostitutes?; (2) the circumstances of their becoming prostitutes; (3) why prostitutes reluctant and hesitant to leave their work and look for other decent jobs; (4) what are their future plans/; (5) will they continue or stop sometime in the future/; and (6) what could probably make them stop being prostitute?